Angiopoietins as Prognostic Markers for Future Kidney Disease and Heart Failure Events after Acute Kidney Injury. Issue 3 (March 2022) - Mansour, Sherry G.; Bhatraju, Pavan K.; Coca, Steven G.; Obeid, Wassim; Wilson, Francis P.; Stanaway, Ian B.; Jia, Yaqi; Thiessen-Philbrook, Heather; Go, Alan S.; Ikizler, T. Alp; Siew, Edward D.; Chinchilli, Vernon M.; et al.
Significance Statement: Mechanisms underlying long-term effects after AKI remain unclear. Because vessel instability is an early response to endothelial injury, the authors studied markers of blood vessel homeostasis (the plasma angiopoietins angiopoietin-1 and angiopoietin-2) in a multicenter prospective cohort that included 1503 adults, half of whom had AKI. Three months after hospitalization, the highest quartile of plasma angiopoietin-1:angiopoietin-2 ratio compared with the lowest quartile associated with 72% less risk of CKD progression, 94% less risk of heart failure, and 82% less risk of death among those with AKI; those without AKI exhibited similar but less pronounced reductions in risk of heart failure and mortality. Angiopoietins may serve as a common pathway to explain the progression of kidney and heart disease after AKI and may point to potential future interventions. Visual Abstract: Abstract : Background: The mechanisms underlying long-term sequelae after AKI remain unclear. Vessel instability, an early response to endothelial injury, may reflect a shared mechanism and early trigger for CKD and heart failure. Methods: To investigate whether plasma angiopoietins, markers of vessel homeostasis, are associated with CKD progression and heart failure admissions after hospitalization in patients with and without AKI, we conducted a prospective cohort study to analyze the balance between angiopoietin-1 (Angpt-1), which maintains vessel stability, and angiopoietin-2 (Angpt-2), which increases vessel destabilization. Three months after discharge, we evaluated the associations between angiopoietins and development of the primary outcomes of CKD progression and heart failure and the secondary outcome of all-cause mortality 3 months after discharge or later. Results: Median age for the 1503 participants was 65.8 years; 746 (50%) had AKI. Compared with the lowest quartile, the highest quartile of the Angpt-1:Angpt-2 ratio was associated with 72% lower risk of CKD progression (adjusted hazard ratio [aHR], 0.28; 95% confidence interval [CI], 0.15 to 0.51), 94% lower risk of heart failure (aHR, 0.06; 95% CI, 0.02 to 0.15), and 82% lower risk of mortality (aHR, 0.18; 95% CI, 0.09 to 0.35) for those with AKI. Among those without AKI, the highest quartile of Angpt-1:Angpt-2 ratio was associated with 71% lower risk of heart failure (aHR, 0.29; 95% CI, 0.12 to 0.69) and 68% less mortality (aHR, 0.32; 95% CI, 0.15 to 0.68). There were no associations with CKD progression. Conclusions: A higher Angpt-1:Angpt-2 ratio was strongly associated with less CKD progression, heart failure, and mortality in the setting of AKI.